A vida de pessoas cegas em Aracaju - Carvalho, Clarissa Andrade (2010)
The present study reports a social experience involving blind people in Aracaju and was carried out from 2004 to 2009. This research related knowing how they organize their lives with regards to: representations, feelings, values, the belonging network and historic action. Starting from the principal that any blind person, as well as any other person, should have the possibility of leading a life of their own, and therefore ought to rely on support from the State and Society, as much as in meeting their essential needs, such as safe feeding, dwelling, education, transport, leisure, engineering and proper urban spaces, as in taking part in the socioeconomic, cultural and political organization of the country, through work and other creative activities. All subjects within this study have acquired blindness and this study derived from people s own understanding. The theoretical perspective is well-founded upon Edward Palmer Thompson, who places the subject in the center of the historical process, and regards their action as a response to their needs, which outlines their way of life. This study encompasses a qualitative approach, and life history was its methodological tool for data gathering. While depicting the ways and means by which these people organize their lives, socially interacting, constructing their practices and identities, I well hope to contribute toward improving protection and promotion measures currently adopted in Aracaju concerning this social segment